Corrosion-resistant aluminum alloy support and machining process thereof
By adjusting the elemental composition of aluminum alloy and adopting specific processing technology, an aluminum alloy bracket with high corrosion resistance and tensile strength was prepared, which solved the problem of insufficient corrosion resistance in seawater environments and extended the The service life is maintained and excellent mechanical properties are maintained.
Patent Information
- Application Number
- CN202411803701.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-02-07
AI Technical Summary
The existing 6061 aluminum alloy bracket has insufficient corrosion resistance in salt spray environment, resulting in a significant decline in mechanical strength after 3-5 years of use in seawater environment, which is unable to meet the normal use needs.
By adjusting the elemental composition of aluminum alloy, including silicon, magnesium, copper, iron, manganese, chromium, zirconium and niobium, a specific processing technology is adopted, including melting, slag-beating, refining, degassing, stand-alone treatment, homogenization, etc., including melting, slag-beating, refining, degassing, and homogenization. By using steps such as shaping, annealing, solid solution and quenching, aluminum alloy brackets with high corrosion resistance and tensile strength are prepared.
It realizes long-term corrosion resistance of aluminum alloy brackets in seawater acidification environment, extends service life, and maintains excellent mechanical properties, and is suitable for offshore photovoltaic brackets.
Smart Images

Figure BDA0005178661450000111
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aluminum alloy brackets, and in particular to a corrosion-resistant aluminum alloy bracket and a processing technology thereof. Background Art
[0002] Photovoltaic is the abbreviation of solar photovoltaic power generation system, which is a new power generation system that uses the photovoltaic effect of solar cell semiconductor materials to convert solar radiation energy into electrical energy. With the development of society, solar energy as a new type of clean energy has gradually attracted people's attention and achieved great development results. Since solar power generation is affected by geographical distribution, seasonal changes, day and night alternation, and has low energy density, when used on a large scale, it occupies a large area and is difficult to implement. Therefore, most of the locations for solar power generation are chosen in unobstructed places such as deserts or oceans.
[0003] Compared with ground photovoltaic power stations, water-based power stations avoid land restrictions and also play a certain protective role in the ecological environment of water, such as reducing water evaporation and inhibiting the reproduction of algae. In addition, they can be combined with aquaculture to truly realize the comprehensive utilization of resources. Among them, floating power stations on the water surface are the most important application form of water-based power stations, which were developed earlier in foreign countries. There are two modes of water-based photovoltaic brackets: pile foundation fixation and water surface floating, but offshore photovoltaic brackets can only be floating. Basically, they are combined with metal brackets through floating tubes or buoys to fix photovoltaic components and float on the water surface. However, metal brackets will be corroded by seawater if they are immersed in water for a long time, especially algae plants drifting in the sea will entangle and reproduce on the bracket once they are hung on the bracket. The algae plants will photosynthesize to form oxygen, which will aggravate the corrosion of the bracket, and the algae plants will attract marine organisms to gather, further aggravating the corrosion of the bracket.
[0004] There are two common aluminum profiles for photovoltaic brackets on the market: 6063 and 6061. 6063 has lower strength and hardness, and is suitable for the construction of home photovoltaic power stations; 6061 has higher strength and hardness, and is suitable for the construction of large photovoltaic power stations. The corrosion resistance of the existing 6061 aluminum alloy in salt spray environment is only about 400 hours. After 3-5 years of use (determined by seawater environmental conditions, such as salinity, temperature, algae microorganisms, etc.), the mechanical strength of the 6061 aluminum alloy bracket will be greatly reduced due to insufficient corrosion resistance (the surface of the aluminum alloy bracket will be uneven, and serious corrosion will cause cavitation), which cannot meet normal use requirements. Summary of the invention
[0005] In view of the technical problems existing in the prior art, the purpose of the present invention is to provide a corrosion-resistant aluminum alloy bracket and a processing technology thereof, aiming to improve the corrosion resistance of the aluminum alloy bracket and further extend the service life of the aluminum alloy bracket.
[0006] In order to achieve the above-mentioned purpose, the embodiment of the present application proposes a corrosion-resistant aluminum alloy bracket, which comprises the following element components in weight percentage:
[0007] Silicon: 0.45 to 0.65 wt. %;
[0008] Magnesium: 1.6 to 2.0% by weight;
[0009] Copper: 0.6 to 0.8 wt. %;
[0010] Iron: not more than 0.35% by weight;
[0011] Manganese: 0.2 to 0.35% by weight;
[0012] Chromium: 0.05 to 0.15% by weight;
[0013] Zirconium: 0.01 to 0.1 wt. %;
[0014] Niobium: 0.01 to 0.1 wt. %;
[0015] The balance is aluminum.
[0016] The present application also provides a processing technology for a corrosion-resistant aluminum alloy bracket, which includes the following steps:
[0017] Step 1: According to the alloy composition, the raw materials are put into the melting furnace and melted at a temperature of 720-740°C. After the raw materials in the melting furnace are completely melted, electromagnetic stirring is performed for at least 90 minutes to make the chemical composition of the aluminum liquid uniform. Samples are taken for spectral analysis to control the melt composition within the required range;
[0018] Step 2: The obtained aluminum alloy melt is subjected to slagging, refining and degassing treatment; then the molten metal is subjected to static treatment by adopting a high temperature and long time process with dynamic temperature control, firstly the molten metal is heated to 740°C at a rate of 80°C / h, and then the molten metal is heated to 820°C at a rate of 60°C / h after being kept for 10 minutes, and then the molten metal is cooled to 695°C at a rate of 50°C / h after being kept for 8 minutes;
[0019] Furthermore, the refining is to first reduce the temperature in the melting furnace to 670°C ~ 690°C, then add a refining agent into the melting furnace for refining, the refining time is set to 25 minutes, electromagnetic stirring is performed during refining, the amount of the refining agent added is 1.15% of the total weight of the alloy melt, and the moisture content of the refining agent is controlled below 0.3%.
[0020] Preferably, the formula of the refining agent is 3 / 5 hexachloroethane and 2 / 5 sodium fluoroborate.
[0021] Step 3: Preheat the mold to a temperature of 220±10°C. After the upper mold and the lower mold are closed, the treated aluminum alloy melt is injected into the mold cavity. After the aluminum alloy melt is solidified and formed, the mold is demolded to obtain an alloy casting.
[0022] Step 4: homogenize the alloy casting, heat the alloy casting from room temperature to 480-520°C, keep the temperature for 4.5-5.5 hours, and the heating rate is 110-130°C / h;
[0023] Step 5: annealing the alloy casting, heating the alloy casting from room temperature to 440-480°C, keeping the temperature for 2.5-3.5 hours, and heating rate of 110-130°C / h;
[0024] Step 6: Solution treatment of the alloy casting, heating the alloy casting from room temperature to 520-560°C, keeping the temperature for 1-2 hours, and heating rate of 90-110°C / h;
[0025] Step 7: quenching and cooling the alloy casting to a temperature of 15 to 35° C., with a quenching cooling rate of 60 to 80° C. / s. The quenching medium may be liquid and / or gas;
[0026] Step 8: Place the quenched casting into an aging furnace and heat to 160-190°C, keep warm for 4-5 hours, and heat at a rate of 40-60°C / h; then air cool.
[0027] Compared with the prior art, the present invention has the following beneficial effects: the characteristics of the aluminum alloy bracket of the embodiment of the present application are obtained by changing the alloy composition ratio and / or the manufacturing processing method, and the aluminum alloy exhibits good tensile strength (medium strength) and unexpectedly high corrosion resistance; specifically, it can be seen from the test examples of the present application that after 1600 hours of SWAAT-seawater acidification test conducted in accordance with ASTM-G85-94-A3, the surface of the aluminum alloy bracket of the present invention has no obvious change, the corrosion depth is small, and the material tensile strength decrease rate is low. The performance exhibited is suitable for application to offshore photovoltaic brackets, and the photovoltaic bracket prepared thereby is durable and has a long service life. DETAILED DESCRIPTION
[0028] The specific implementation modes of the present invention are further described below in conjunction with examples. The following examples are only used to more clearly illustrate the technical solutions of the present invention, and are not intended to limit the protection scope of the present invention.
[0029] The embodiment of the present application provides a corrosion-resistant aluminum alloy bracket and its processing technology, thereby solving the problem in the prior art that the mechanical strength of the bracket is seriously reduced due to insufficient corrosion resistance of the 6061 aluminum alloy, thereby achieving the effect of extending the service life of the aluminum alloy bracket.
[0030] The technical solution in the embodiment of the present application is to solve the problem of insufficient corrosion resistance of the above-mentioned aluminum alloy. The aluminum alloy bracket comprises the following composition in weight percentage:
[0031] Silicon (Si): 0.45 to 0.65 wt %;
[0032] Magnesium (Mg): 1.6 to 2.0 wt %;
[0033] Copper (Cu): 0.6 to 0.8 wt%;
[0034] Iron (Fe): not more than 0.35% by weight;
[0035] Manganese (Mn): 0.2 to 0.35 wt%;
[0036] Chromium (Cr): 0.05 to 0.15 wt%;
[0037] Zirconium (Zr): 0.01 to 0.1 wt%;
[0038] Niobium (Nb): 0.01 to 0.1 wt%;
[0039] The balance is aluminum (Al).
[0040] In some examples, the alloy compositions described herein include about 1.6% to about 2.0% silicon (Si). For example, the alloy composition needs to include Si, and its content is further about 0.5% to about 0.65%, about 0.55% to about 0.65%, about 0.6% to about 0.65%, about 0.45% to about 0.6%, about 0.45% to about 0.55%, about 0.45% to about 0.5%, about 0.5% to about 0.6%, about 0.5% to about 0.55%, about 0.55% to about 0.6%. In some examples, the alloy composition can include about 0.45%, about 0.46%, about 0.47%, about 0.48%, about 0.49%, about 0.5%, about 0.51%, about 0.52%, about 0.53%, about 0.54%, about 0.55%, about 0.56%, about 0.57%, about 0.58%, about 0.59%, about 0.6%, about 0.61%, about 0.62%, about 0.63%, about 0.64%, or about 0.65% Si, all percentages expressed in wt%.
[0041] In some examples, the alloy compositions described herein include about 1.6% to about 2.0% magnesium (Mg). For example, the alloy composition needs to include Mg, and its content is further about 1.6% to about 1.9%, about 1.6% to about 1.8%, about 1.6% to about 1.7%, about 1.7% to about 2.0%, about 1.8% to about 2.0%, about 1.9% to about 2.0%, about 1.7% to about 1.9%, about 1.7% to about 1.8%, about 1.8% to about 1.9%. In some examples, the alloy composition may include about 1.60%, about 1.61%, about 1.62%, about 1.63%, about 1.64%, about 1.65%, about 1.66%, about 1.67%, about 1.68%, about 1.69%, about 1.70%, about 1.71%, about 1.72%, about 1.73%, about 1.74%, about 1.75%, about 1.76%, about 1.77%, about 1.78%, about 1.79%, about 1.80%, about 1.81%, about 1.82%, about 1.83%, about 1.84%, about 1.85%, about 1.86%, about 1.87%, about 1.88%, about 1.89%, about 1.90%, about 1.91%, about 1.92%, about 1.93%, about 1.94%, about 1.95%, about 1.96%, about 1.97%, about 1.98%, about 1.99%, about 1.10%. %, about 1.80%, about 1.81%, about 1.82%, about 1.83%, about 1.84%, about 1.85%, about 1.86%, about 1.87%, about 1.88%, about 1.89%, about 1.90%, about 1.91%, about 1.92%, about 1.93%, about 1.94%, about 1.95%, about 1.96%, about 1.97%, about 1.98%, about 1.99% or about 2.0% Mg, all percentages are expressed in wt%.
[0042] In some examples, the alloy compositions described herein include copper (Cu) in an amount of about 0.6% to about 0.8%. For example, the alloy compositions may include Cu in an amount of about 0.6% to about 0.75%, about 0.6% to about 0.7%, about 0.6% to about 0.65%, about 0.65% to about 0.8%, about 0.7% to about 0.8%, about 0.75% to about 0.8%, about 0.65% to about 0.75%, about 0.65% to about 0.7%, about 0.7% to about 0.75%. In some examples, the alloy composition can include about 0.60%, about 0.61%, about 0.62%, about 0.63%, about 0.64%, about 0.65%, about 0.66%, about 0.67%, about 0.68%, about 0.69%, about 0.70%, about 0.71%, about 0.72%, about 0.73%, about 0.74%, about 0.75%, about 0.76%, about 0.77%, about 0.78%, about 0.79%, or about 0.80% Cu, all percentages expressed in wt%.
[0043] In some examples, the alloy compositions described herein include about 0 to about 0.35% iron (Fe). For example, the alloy compositions may include Fe, and its content is further about 0 to about 0.30%, about 0 to about 0.25%, about 0 to about 0.20%, about 0 to about 0.15%, about 0 to about 0.10%, about 0 to about 0.05%, about 0.05% to about 0.35%, about 0.10% to about 0.35%, about 0.15% to about 0.35%, about 0.20% to about 0.35%, about 0.25% to about 0.35%, about 0.30% to about 0.35%, about 0.05% to about 0.30 ...5%, about 0.10% to about 0.35%, about 0.15% to about 0.35%, about 0.20% to about 0.35%, about 0.25% to about 0.35%, about 0.30% to about 0.35%, About 0.25%, about 0.05% to about 0.20%, about 0.05% to about 0.15%, about 0.05% to about 0.10%, about 0.10% to about 0.30%, about 0.15% to about 0.30%, about 0.20% to about 0.30%, about 0.25% to about 0.30%, about 0.10% to about 0.25%, about 0.10% to about 0.20%, about 0.10% to about 0.15%, about 0.15% to about 0.25%, about 0.20% to about 0.25%, about 0.15% to about 0.20%. In some examples, the alloy composition may include about 0, about 0.01%, about 0.02%, about 0.03%, about 0.04%, about 0.05%, about 0.06%, about 0.07%, about 0.08%, about 0.09%, about 0.10%, about 0.11%, about 0.12%, about 0.13%, about 0.14%, about 0.15%, about 0.16%, about 0.17%, about 0.18%, about 0.20%, about 0.21%, about 0.22%, about 0.23%, about 0.24%, about 0.25%, about 0.26%, about 0.27%, about 0.28%, about 0.29%, about 0.30%, about 0.31%, about 0.32%, about 0.33%, about 0.34%, about 0.35%, about 0.36%, about 0.37%, about 0.38%, about 0.39%, about 0.40%, about 0.41%, about 0.42%, about 0.43%, about 0.44%, about 0.45%, about 0.46%, about 0.47%, about 0.48%, about 0.49%, about 0.50%, about 0.51%, about 0.52%, about 0.53%, about 0.54%, about 0.55%, about 0.56%, about 0.57%, about 0.58%, about 0.59%, about 0. .18%, about 0.19%, about 0.20%, about 0.21%, about 0.22%, about 0.23%, about 0.24%, about 0.25%, about 0.26%, about 0.27%, about 0.28%, about 0.29%, about 0.30%, about 0.31%, about 0.32%, about 0.33%, about 0.34% or about 0.35% Fe, all percentages are expressed in wt%.
[0044] In some examples, the alloy compositions described herein include about 0.2% to about 0.35% manganese (Mn). For example, the alloy composition needs to include Mn, and its content is further about 0.2% to about 0.3%, about 0.2% to about 0.25%, about 0.25% to about 0.35%, about 0.3% to about 0.35%, about 0.25% to about 0.3%. In some examples, the alloy composition may include about 0.20%, about 0.21%, about 0.22%, about 0.23%, about 0.24%, about 0.25%, about 0.26%, about 0.27%, about 0.28%, about 0.29%, about 0.30%, about 0.31%, about 0.32%, about 0.33%, about 0.34%, or about 0.35% Mn, all percentages are expressed in wt%.
[0045] In some examples, the alloy compositions described herein include about 0.05% to about 0.15% chromium (Cr). For example, the alloy composition needs to include Cr, and its content is further about 0.06% to about 0.14%, 0.07% to about 0.13%, 0.08% to about 0.12%, 0.09% to about 0.11%, 0.05% to about 0.10%, 0.10% to about 0.15%. In some examples, the alloy composition may include about 0.05%, about 0.06%, about 0.07%, about 0.08%, about 0.09%, about 0.10%, about 0.11%, about 0.12%, about 0.13%, about 0.14%, or about 0.15% Cr, all percentages are expressed in wt%.
[0046] In some examples, the alloy compositions described herein include about 0.01% to about 0.1% zirconium (Zr). For example, the alloy composition needs to include Zr, and its content is further about 0.02% to about 0.09%, 0.03% to about 0.08%, 0.04% to about 0.07%, 0.05% to about 0.06%, 0.01% to about 0.05%, 0.05% to about 0.10%. In some examples, the alloy composition may include about 0.01%, about 0.02%, about 0.03%, about 0.04%, about 0.05%, about 0.06%, about 0.07%, about 0.08%, about 0.09% or about 0.10% Zr, all percentages are expressed in wt%.
[0047] In some examples, the alloy compositions described herein include about 0.01% to about 0.1% niobium (Nb). For example, the alloy composition needs to include Nb, and its content is further about 0.02% to about 0.09%, 0.03% to about 0.08%, 0.04% to about 0.07%, 0.05% to about 0.06%, 0.01% to about 0.05%, 0.05% to about 0.10%. In some examples, the alloy composition may include about 0.01%, about 0.02%, about 0.03%, about 0.04%, about 0.05%, about 0.06%, about 0.07%, about 0.08%, about 0.09%, or about 0.10% Nb, all percentages are expressed in wt%.
[0048] In addition, the alloy compositions disclosed herein may include other trace element components referred to as impurities in an amount of 0.05% or less, 0.04% or less, 0.03% or less, 0.02% or less, or 0.01% or less. These impurities may include, but are not limited to, Ga, Ca, Bi, Na, Pb, or a combination thereof. Thus, Ga, Ca, Bi, Na, or Pb may be present in the alloy in an amount of 0.05% or less, 0.04% or less, 0.03% or less, 0.02% or less, or 0.01% or less. The sum of all impurities does not exceed 0.15%, and all percentages are expressed in wt%.
[0049] The aluminum alloy bracket production and processing technology described in the embodiment of the present application mainly includes the following steps:
[0050] Step 1: According to the alloy composition, the raw materials (high-purity aluminum ingots, magnesium ingots, and aluminum-silicon master alloys, aluminum-copper master alloys, aluminum-iron master alloys, aluminum-manganese master alloys, aluminum-chromium master alloys, aluminum-zirconium master alloys, and aluminum-niobium master alloys) are placed in a melting furnace and melted at a temperature of 720 to 740°C. After the raw materials in the melting furnace are completely melted, electromagnetic stirring is performed for at least 90 minutes to make the chemical composition of the aluminum liquid uniform, and samples are taken for spectral analysis to control the melt composition within the required range;
[0051] Step 2: slagging, refining and degassing the obtained aluminum alloy melt; wherein, the refining is to first reduce the temperature in the melting furnace to 670°C-690°C, then add a refining agent into the melting furnace for refining, the refining time is set to 25 minutes, electromagnetic stirring is performed during refining, the amount of the refining agent added is 1.15% of the total weight of the alloy melt, the moisture content of the refining agent is controlled below 0.3%, and the formula of the refining agent is 3 / 5 hexachloroethane and 2 / 5 sodium fluoroborate; then, a high-temperature and long-time process with dynamic temperature control is used to statically treat the refined molten metal, and the specific operation is: first, the molten metal is heated to 740°C at a rate of 80°C / h, and then the molten metal is heated to 820°C at a rate of 60°C / h after 10 minutes of heat preservation, and then the molten metal is cooled to 695°C at a rate of 50°C / h after 8 minutes of heat preservation;
[0052] Step 3: Preheat the mold to a temperature of 220±10°C. After the upper mold and the lower mold are closed, the treated aluminum alloy melt is injected into the mold cavity. After the aluminum alloy melt is solidified and formed, the mold is demolded to obtain an alloy casting.
[0053] Step 4: homogenizing the alloy casting, heating the alloy casting from room temperature to 480-520°C, keeping the temperature for 4.5-5.5 hours, and heating rate of 110-130°C / h; in some examples, the homogenization temperature is about 480°C to about 490°C, about 485°C to about 495°C, about 490°C to about 500°C, about 495°C to about 505°C, about 500°C to about 510°C, about 505°C to about 515°C, about 510°C to about 520°C, about 485°C to about 515°C, about 590°C to about 510°C, about 595°C to about ℃ to about 505℃; in some instances, the homogenization treatment heat preservation time is about 4.5 hours, about 4.6 hours, about 4.7 hours, about 4.8 hours, about 4.9 hours, about 5.0 hours, about 5.1 hours, about 5.2 hours, about 5.3 hours, about 5.4 hours, about 5.5 hours; in some instances, the heating rate of the homogenization treatment is about 110℃ / h to about 115℃ / h, about 115℃ / h to about 120℃ / h, about 120℃ / h to about 125℃ / h, about 125℃ / h to about 130℃ / h.
[0054] Step 5: annealing the alloy casting, heating the alloy casting from room temperature to 440-480°C, keeping the temperature for 2.5-3.5 hours, and the heating rate is 110-130°C / h; in some examples, the annealing temperature is about 440°C to about 450°C, about 445°C to about 455°C, about 450°C to about 460°C, about 455°C to about 465°C, about 460°C to about 470°C, about 465°C to about 475°C, about 470°C to about 480°C, about 445°C to about 475°C, about 450°C to about 470°C, about 455°C to about 465°C, about 460°C to about 470°C, about 465°C to about 475°C, about 470°C to about 480°C, about 445°C to about 475°C, about 450°C to about 470°C, about 455°C to about 465°C ℃ to about 465℃; in some instances, the annealing treatment has a soaking time of about 2.5 hours, about 2.6 hours, about 2.7 hours, about 2.8 hours, about 2.9 hours, about 3.0 hours, about 3.1 hours, about 3.2 hours, about 3.3 hours, about 3.4 hours, or about 3.5 hours; in some instances, the annealing treatment has a heating rate of about 110℃ / h to about 115℃ / h, about 115℃ / h to about 120℃ / h, about 120℃ / h to about 125℃ / h, or about 125℃ / h to about 130℃ / h.
[0055] Step 6: Solution treat the alloy casting, heat the alloy casting from room temperature to 520-560°C, keep warm for 1-2 hours, and the heating rate is 90-110°C / h; in some examples, the homogenization temperature is about 520°C to about 530°C, about 525°C to about 535°C, about 530°C to about 540°C, about 535°C to about 545°C, about 540°C to about 550°C, about 545°C to about 555°C, about 550°C to about 560°C, about 525°C to about 555°C, about 530°C to about 550°C, about 535°C to about 545°C. In some instances, the solution treatment soaking time is about 1 hour, about 1.1 hours, about 1.2 hours, about 1.3 hours, about 1.4 hours, about 1.5 hours, about 1.6 hours, about 1.7 hours, about 1.8 hours, about 1.9 hours, or about 2.0 hours; in some instances, the solution treatment heating rate is about 90°C / h to about 95°C / h, about 95°C / h to about 100°C / h, about 100°C / h to about 105°C / h, or about 105°C / h to about 110°C / h.
[0056] Step 7: The alloy casting is then quenched and cooled to a temperature of 15 to 35°C, with a quenching cooling rate of 60 to 80°C / s. The quenching medium can be liquid and / or gas. In one example, the alloy casting can be rapidly quenched by water; in one example, the alloy casting can be rapidly quenched by air; in some examples, the quenching cooling rate is about 60°C / s, about 61°C / s, about 62°C / s, about 63°C / s, about 64°C / s, about 65°C / s, about 66°C / s, about 67°C / s, about 68°C / s, about 69°C / s, about 70°C / s, about 71°C / s, about 72°C / s, about 73°C / s, about 74°C / s, about 75°C / s, about 76°C / s, about 77°C / s, about 78°C / s, about 79°C / s, or about 80°C / s.
[0057] Step 8: Place the quenched casting in an aging furnace and heat it to 160-190°C, keep it warm for 4-5 hours, and the heating rate is 40-60°C / h; then air cool; in some examples, the aging treatment temperature is about 160°C to about 165°C, about 165°C to about 170°C, about 170°C to about 175°C, about 175°C to about 180°C, about 180°C to about 185°C, about 185°C to about 190°C, about 165°C to about 185°C, about 170°C to about 180°C; in one In some examples, the soaking time for the aging treatment is about 4 hours, about 4.1 hours, about 4.2 hours, about 4.3 hours, about 4.4 hours, about 4.5 hours, about 4.6 hours, about 4.7 hours, about 4.8 hours, about 4.9 hours, or about 5.0 hours; in some examples, the heating rate for the aging treatment is about 40°C / h to about 45°C / h, about 45°C / h to about 50°C / h, about 50°C / h to about 55°C / h, or about 55°C / h to about 60°C / h.
[0058] In one example, the surface of the aluminum alloy bracket may also be subjected to anti-corrosion treatment, including but not limited to anodizing, passivation, spray coating, and electrodeposition coating.
[0059] Example 1
[0060] An aluminum alloy bracket comprises the following elemental components in weight percentage:
[0061] Si-0.45%, Mg-1.6%, Cu-0.6%, Mn-0.2%, Cr-0.05%, Zr-0.01%, Nb-0.01% and the balance Al.
[0062] Example 2
[0063] An aluminum alloy bracket comprises the following elemental components in weight percentage:
[0064] Si-0.5%, Fe-0.05%, Mg-1.7%, Cu-0.65%, Mn-0.22%, Cr-0.07%, Zr-0.03%, Nb-0.03% and the balance Al.
[0065] Example 3
[0066] An aluminum alloy bracket comprises the following elemental components in weight percentage:
[0067] Si-0.55%, Fe-0.15%, Mg-1.8%, Cu-0.7%, Mn-0.25%, Cr-0.10%, Zr-0.05%, Nb-0.05% and the balance Al.
[0068] Example 4
[0069] An aluminum alloy bracket comprises the following elemental components in weight percentage:
[0070] Si-0.60%, Fe-0.25%, Mg-1.9%, Cu-0.75%, Mn-0.3%, Cr-0.12%, Zr-0.08%, Nb-0.07% and the balance Al.
[0071] Example 5
[0072] An aluminum alloy bracket comprises the following elemental components in weight percentage:
[0073] Si-0.65%, Fe-0.35%, Mg-2.0%, Cu-0.8%, Mn-0.35%, Cr-0.15%, Zr-0.1%, Nb-0.1% and the balance Al.
[0074] Example 6
[0075] An aluminum alloy bracket comprises the following elemental components in weight percentage:
[0076] Si-0.45%, Fe-0.15%, Mg-1.8%, Cu-0.7%, Mn-0.3%, Cr-0.15%, Zr-0.08%, Nb-0.06% and the balance Al.
[0077] Comparative Example 1
[0078] An aluminum alloy bracket comprises the following elemental components in weight percentage:
[0079] Si - 0.8% , Fe-0.15%, Mg-1.8%, Cu-0.7%, Mn-0.3%, Cr-0.15%, Zr-0.08%, Nb-0.06% and the balance Al.
[0080] Comparative Example 2
[0081] An aluminum alloy bracket comprises the following elemental components in weight percentage:
[0082] Si-0.45%, Fe-0.7% , Mg-1.8%, Cu-0.7%, Mn-0.3%, Cr-0.15%, Zr-0.08%, Nb-0.06% and the balance Al.
[0083] Comparative Example 3
[0084] An aluminum alloy bracket comprises the following elemental components in weight percentage:
[0085] Si-0.45%, Fe-0.15%, Mg-1.8%, Cu - 0.15% , Mn-0.3%, Cr-0.15%, Zr-0.08%, Nb-0.06% and the balance Al.
[0086] Comparative Example 4
[0087] An aluminum alloy bracket comprises the following elemental components in weight percentage:
[0088] Si-0.45%, Fe-0.15%, Mg-0.8% , Cu-0.7%, Mn-0.3%, Cr-0.15%, Zr-0.08%, Nb-0.06% and the balance Al.
[0089] Comparative Example 5
[0090] An aluminum alloy bracket comprises the following elemental components in weight percentage:
[0091] Si-0.45%, Fe-0.7%, Mg-1.8%, Cu-0.15%, Mn-0.3%, Cr-0.15%, Nb-0.06% and the balance Al.
[0092] Comparative Example 6
[0093] An aluminum alloy bracket comprises the following elemental components in weight percentage:
[0094] Si-0.45%, Fe-0.7%, Mg-0.8%, Cu-0.15%, Mn-0.3%, Cr-0.15%, Zr-0.08% and the balance Al.
[0095] Comparative Example 7
[0096] A 6061 type aluminum alloy comprising the following elemental compositions in weight percent:
[0097] Cu: 0.15-0.4, Mn: 0.15, Mg: 0.8-1.2, Zn: 0.25, Cr: 0.04-0.35, Ti: 0.15, Si: 0.4-0.8, Fe: 0.7 and the balance of Al.
[0098] Test example
[0099] The aluminum alloy brackets obtained in Examples 1-6 were used as test samples #1-#6, and the aluminum alloy brackets obtained in Comparative Examples 1-7 were used as control samples &1-&7.
[0100] Test method:
[0101] 1) Corrosion resistance test: Corrosion resistance evaluation (SWAAT - Seawater Acidification Test) was carried out according to ASTM-G85-94-A3. Specifically, each test sample and control sample were placed in a closed chamber and exposed to a climate change consisting of the following two parts of repeated cycles: first, continuous indirect spraying of acidified (pH 2.8 to 3.0) synthetic seawater solution for 30 minutes, the solution was sprayed at 1.0 to 2.0 ml / 80 cm 2 / h rate falls on the sample; followed by 90 minutes of exposure to a high humidity climate above 98% RH. The entire test cycle is carried out at a constant chamber temperature of +49°C, and the number of cycles repeated is 200 times (400 hours), 400 times (800 hours), and 800 times (1600 hours) in turn, and the sample is observed for any abnormalities. Finally, each test sample and control sample is subjected to metallographic microscopic observation, and the corrosion depth of each sample is recorded. The average value is the corrosion depth of the corresponding test sample or control sample, which is recorded in Table 1 below;
[0102] 2) Tensile strength test: Test samples #1-#6 and control samples &1-&7 (seawater acidification test 0 hours, 400 hours, 800 hours, 1600 hours) were processed into standard specimens according to the requirements of GB6397-86 "Metal Tensile Test Specimens", and then tensile tests were carried out using a tensile testing machine. Three standard specimens were made for each sample for testing, and the average value of the test results was taken as the tensile strength of the corresponding test sample or control sample, which was recorded in the following Table 1.
[0103] Table 1: Test results of test samples #1-#6 and control samples &1-&7
[0104]
[0105] From the data recorded in Table 1 above, the aluminum alloy bracket prepared in the embodiment of the present application has better corrosion resistance and tensile strength than the comparative example (only for comparative examples 1-6), which can ensure that the aluminum alloy bracket has excellent and stable mechanical strength when used for a long time in a corrosive environment, and significantly improves the service life of the product.
[0106] Further, it can be seen from Table 1 that the surface corrosion and tensile strength of the samples of the embodiment and the comparative example did not change in the interval of less than or equal to 400 hours of seawater acidification test. When the seawater acidification test time reached 800 hours, each sample showed different degrees of corrosion and slight weakening of tensile strength, but the corrosion degree of the sample of the embodiment was much less than that of the comparative example, and the tensile strength of the embodiment did not decrease due to the small degree of corrosion. When the seawater acidification test time reached 1600 hours, the comparative example sample showed severe corrosion, accompanied by a significant weakening of the tensile strength of the material (the decrease rate was 5.80% to 22.62%), while the corrosion of the sample of the embodiment of the present application was not serious, and the decrease rate of the tensile strength of the material was only 1.33% to 2.71%, which shows that the aluminum alloy material of the embodiment will have better safety, reliability and longer service life when used as an offshore floating photovoltaic bracket.
[0107] It can be seen from the comparative example group that the tensile strength and corrosion resistance of the aluminum alloy bracket prepared in the embodiment of the present application are affected by the raw material ratio. The aluminum alloy material prepared by selecting the element content within the protection scope of the present application obviously has better tensile strength and corrosion resistance. If the content of each element component is not within the protection scope of the present application, or some components are out of the formula, or the content of some element components does not meet the requirements, the mechanical properties and corrosion resistance of the aluminum alloy bracket finally obtained cannot achieve the expected effect.
[0108] Compared with the aluminum alloy bracket of the embodiment of the present application, Comparative Example 7 involves a 6061 aluminum alloy material, the magnesium content of the 6061 aluminum alloy is lower than that of the present application, the copper content is lower than that of the present application, the iron content is higher than that of the present application, the manganese content is lower than that of the present application, and the 6061 aluminum alloy also contains zinc and titanium elements not included in the embodiment of the present application, and the 6061 aluminum alloy does not contain zirconium and niobium elements in the embodiment of the present application. Although the original tensile strength of the 6061 aluminum alloy is better than that of the aluminum alloy of the embodiment of the present application, the corrosion resistance of the 6061 aluminum alloy is far less than that of the embodiment of the present application, resulting in a significantly greater rate of decrease in its tensile strength than that of the embodiment of the present application. Therefore, in the long run, the durability of the 6061 aluminum alloy used in the offshore floating photovoltaic bracket is not as good as that of the aluminum alloy bracket of the embodiment of the present application.
[0109] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A corrosion-resistant aluminum alloy bracket, characterized in that: Contains the following elemental composition by weight percentage: Silicon: 0.45 to 0.65 wt. %; Magnesium: 1.6 to 2.0% by weight; Copper: 0.6 to 0.8 wt. %; Iron: not more than 0.35% by weight; Manganese: 0.2 to 0.35% by weight; Chromium: 0.05 to 0.15% by weight; Zirconium: 0.01 to 0.1 wt. %; Niobium: 0.01 to 0.1 wt. %; The balance is aluminum.
2. The corrosion-resistant aluminum alloy bracket according to claim 1, characterized in that: Contains the following elemental composition by weight percentage: Si-0.45%, Mg-1.6%, Cu-0.6%, Mn-0.2%, Cr-0.05%, Zr-0.01%, Nb-0.01% and the balance Al.
3. The corrosion-resistant aluminum alloy bracket according to claim 1, characterized in that: Contains the following elemental composition by weight percentage: Si-0.5%, Fe-0.05%, Mg-1.7%, Cu-0.65%, Mn-0.22%, Cr-0.07%, Zr-0.03%, Nb-0.03% and the balance Al.
4. The corrosion-resistant aluminum alloy bracket according to claim 1, characterized in that: Contains the following elemental composition by weight percentage: Si-0.55%, Fe-0.15%, Mg-1.8%, Cu-0.7%, Mn-0.25%, Cr-0.10%, Zr-0.05%, Nb-0.05% and the balance Al.
5. The corrosion-resistant aluminum alloy bracket according to claim 1, characterized in that: Contains the following elemental composition by weight percentage: Si-0.60%, Fe-0.25%, Mg-1.9%, Cu-0.75%, Mn-0.3%, Cr-0.12%, Zr-0.08%, Nb-0.07% and the balance Al.
6. The corrosion-resistant aluminum alloy bracket according to claim 1, characterized in that: Contains the following elemental composition by weight percentage: Si-0.65%, Fe-0.35%, Mg-2.0%, Cu-0.8%, Mn-0.35%, Cr-0.15%, Zr-0.1%, Nb-0.1% and the balance Al.
7. The corrosion-resistant aluminum alloy bracket according to claim 1, characterized in that: Contains the following elemental composition by weight percentage: Si-0.45%, Fe-0.15%, Mg-1.8%, Cu-0.7%, Mn-0.3%, Cr-0.15%, Zr-0.08%, Nb-0.06% and the balance Al.
8. A processing technology for a corrosion-resistant aluminum alloy bracket according to any one of claims 1 to 7, characterized in that: The following steps are involved: Step 1: According to the alloy composition, the raw materials are put into the melting furnace and melted at a temperature of 720-740°C. After the raw materials in the melting furnace are completely melted, electromagnetic stirring is performed for at least 90 minutes to make the chemical composition of the aluminum liquid uniform. Samples are taken for spectral analysis to control the melt composition within the required range; Step 2: The obtained aluminum alloy melt is subjected to slagging, refining and degassing treatment; then the molten metal is subjected to static treatment by adopting a high temperature and long time process with dynamic temperature control, firstly the molten metal is heated to 740°C at a rate of 80°C / h, and then the molten metal is heated to 820°C at a rate of 60°C / h after being kept for 10 minutes, and then the molten metal is cooled to 695°C at a rate of 50°C / h after being kept for 8 minutes; Step 3: Preheat the mold to a temperature of 220±10°C. After the upper mold and the lower mold are closed, the treated aluminum alloy melt is injected into the mold cavity. After the aluminum alloy melt is solidified and formed, the mold is demolded to obtain an alloy casting. Step 4: homogenize the alloy casting, heat the alloy casting from room temperature to 480-520°C, keep the temperature for 4.5-5.5 hours, and the heating rate is 110-130°C / h; Step 5: annealing the alloy casting, heating the alloy casting from room temperature to 440-480°C, keeping the temperature for 2.5-3.5 hours, and heating rate of 110-130°C / h; Step 6: Solution treatment of the alloy casting, heating the alloy casting from room temperature to 520-560°C, keeping the temperature for 1-2 hours, and heating rate of 90-110°C / h; Step 7: quenching and cooling the alloy casting to a temperature of 15 to 35° C., with a quenching cooling rate of 60 to 80° C. / s. The quenching medium may be liquid and / or gas; Step 8: Place the quenched casting into an aging furnace and heat to 160-190°C, keep warm for 4-5 hours, and heat at a rate of 40-60°C / h; then air cool.
9. The corrosion-resistant aluminum alloy bracket according to claim 8, characterized in that: The refining is to first reduce the temperature in the melting furnace to 670°C-690°C, then add a refining agent into the melting furnace for refining, the refining time is set to 25 minutes, electromagnetic stirring is performed during refining, the amount of the refining agent added is 1.15% of the total weight of the alloy melt, and the moisture content of the refining agent is controlled below 0.3%.
10. The corrosion-resistant aluminum alloy bracket according to claim 8, characterized in that: The formula of the refining agent is 3 / 5 hexachloroethane and 2 / 5 sodium fluoroborate.